Pengaruh Produk, Harga, Tempat, Dan Promosi Terhadap Keputusan Pembelian Smartphone Samsung (Studi Kasus Pada Warga Hutumuri) - Gloria Hursepuny; Sautman (Fakultas Ekonomi Universitas Kristen Indonesia, 2023)
This study is motivated by a decline in sales of Samsung smartphones over the period 2020-2021. This decrease in sales indicates a decrease in consumer purchasing decisions on Samsung smartphone products so that it can be formulated in this study that how consumers make decisions to purchase Samsung smartphones in the midst of the phenomenon of increasingly fierce competition based on the marketing mix, namely product, price, place, and promotion. The purpose of this study is to investigate whether the product, price, place, and promotion of Samsung smartphones have a significant effect on the decision to purchase Samsung smartphones by Hutumuri residents. Knowing this allows producers to maintain or improve their strategy. In this study, a quantitative approach was used by distributing questionnaires for data collection using the Likert scale, and an incidental sampling technique was used to determine the sample used for 50 respondents. The analytical methods used were validity tests, reliability tests, classical assumption tests, and multiple linear regression tests. Results of processing SPSS data on the impact of product, price, place and promotion on purchasing decisions. This test showed that one variable, the product variable, had a positive but insignificant effect on the purchase decision, and the promotion variable had a positive and significant effect on the purchase decision. And two variables: variable, price, and place do not influence the purchase decision, This is obtained because these two variables have a negative and insignificant effect. Simultaneous testing (Test F) shows that the variable product, price, place, and promotion together influence the decision to buy a Samsung smartphone in Hutumuri.The coefficient of determination (R-squared) is 0.565. This means that product, price, place, and promotional variables can explain 0.565% or 56.5% of purchasing decisions, with the remaining 43.5% being influenced by unresearched factors. Keywords: Product, Price, Place, and Promotion, Purchase Decision, Samsung Smartphone